2017
DOI: 10.1177/0033294117741654
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Relationship Between Resilience and Big Five Personality Traits in Japanese Adolescents

Abstract: Prior work has indicated that female adolescents mature more quickly than males with regard to the various personality dimensions. From the developmental perspectives, this study aimed to explore gender differences in the relationships between resilience and the Big Five personality traits in Japanese adolescents. Middle school students ( N = 310, 155 females, age range = 14-15 years) participated in an online survey. The results demonstrated that females had higher Conscientiousness than males. Stepwise regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 29 publications
1
32
2
1
Order By: Relevance
“…However, girls reported higher resilience under adverse life conditions showing higher competence and enculturation scores in a study conducted among migrant Indian youths living in America 39. Adolescent girls in Japan also reported higher resilience 40. This may again reflect the socio-cultural contexts – where there is greater gender equity, with greater flexibility in roles and opportunities for girls and women, girls report higher resilience.…”
Section: Discussionmentioning
confidence: 90%
“…However, girls reported higher resilience under adverse life conditions showing higher competence and enculturation scores in a study conducted among migrant Indian youths living in America 39. Adolescent girls in Japan also reported higher resilience 40. This may again reflect the socio-cultural contexts – where there is greater gender equity, with greater flexibility in roles and opportunities for girls and women, girls report higher resilience.…”
Section: Discussionmentioning
confidence: 90%
“…With respect to personality, positive associations between trait resilience and extraversion, openness to experience, agreeableness and conscientiousness and negative associations with neuroticism have been reported in adults 16,17,23 . However, the few studies that have been conducted in adolescents reveal inconsistent associations 2527 . Indeed, among Japanese adolescents, neuroticism was predictive of resilience only among females and extraversion only among males 25 , and in a study of Italian adolescents another personality factor, dispositional optimism, was positively associated with resilience 28 .…”
Section: Reconceptualization Of Resiliencementioning
confidence: 99%
“…However, the few studies that have been conducted in adolescents reveal inconsistent associations 2527 . Indeed, among Japanese adolescents, neuroticism was predictive of resilience only among females and extraversion only among males 25 , and in a study of Italian adolescents another personality factor, dispositional optimism, was positively associated with resilience 28 . However, and crucially, in all of these studies, resilience is assessed outside the context of adversity and therefore, this research does not necessarily inform us as to how resilience emerges in response to adversity.…”
Section: Reconceptualization Of Resiliencementioning
confidence: 99%
“…On the other hand, Shi et al (2015) reported that there is no association between resilience and neuroticism. In another study conducted by Iimura and Taku (2018), it was observed that females have a higher conscientiousness than males. In the case of adolescents, Fayombo (2010) observed conscientiousness as the best predictor of resilience, followed by agreeableness, openness and neuroticism.…”
Section: Big Five Personality Model and Emotional Resiliencementioning
confidence: 94%
“…All these studies suggest an inconsistent relationship between Big Five personality factors and resilience. There are a couple of reasons cited in literature that indicate variation in findings may be due to: (a) adolescencespecific gender differences (Iimura & Taku, 2018;Weisberg et al, 2011), (b) genetic factors (Amstadter et al, 2016), (c) cultural differences (Eley et al, 2013) and (d) socioeconomic adversity (Malhi et al, 2019).…”
Section: Big Five Personality Model and Emotional Resiliencementioning
confidence: 99%